2022
DOI: 10.3390/rs14112602
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Hyperspectral and Machine Learning to Invert Soil Electrical Conductivity

Abstract: An accurate estimation of soil electrical conductivity (EC) using hyperspectral techniques is of great significance for understanding the spatial distribution of solutes and soil salinization. Although spectral transformation has been widely used in data pre-processing, the performance of different pre-processing techniques (or combination methods) on different models of the same data set is still ambiguous. Moreover, extremely randomized trees (ERT) and light gradient boosting machine (LightGBM) models are ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 63 publications
1
5
0
Order By: Relevance
“…In addition, the numerical two-dimensional contour map of the correlation between spectral index and salinity can provide comprehensive information regarding the ability of two different wavelength combinations to predict soil properties [33]. It has been pointed out that the second derivative of spectral reflectance is the best way to calculate the two-dimensional salinity index [34]; therefore, 2D correlation maps after the second derivative of reflectance were used to determine the relationship between the difference index (DI), the ratio index (RI), the normalized index (NDI), and the soil EC (Table 1).…”
Section: Selection Of the Optimal Spectral Index For Estimating Soil ...mentioning
confidence: 99%
“…In addition, the numerical two-dimensional contour map of the correlation between spectral index and salinity can provide comprehensive information regarding the ability of two different wavelength combinations to predict soil properties [33]. It has been pointed out that the second derivative of spectral reflectance is the best way to calculate the two-dimensional salinity index [34]; therefore, 2D correlation maps after the second derivative of reflectance were used to determine the relationship between the difference index (DI), the ratio index (RI), the normalized index (NDI), and the soil EC (Table 1).…”
Section: Selection Of the Optimal Spectral Index For Estimating Soil ...mentioning
confidence: 99%
“…In [38], it is shown that a similar approach though using a different algorithm, XGBoost, can be used to estimate agricultural soil moisture content. And in [39], XGBoost, LightGBM, Random Forests, and other algorithms are used to predict the soil electrical conductivity from hyperspectral data using fractional-derivative-augmented data. Though related, but not necessarily an agricultural application, is discussed in [40], where augmented hyperspectral data is used to estimate the clay content in desert soils using partial least squares regression.…”
Section: Spectroscopymentioning
confidence: 99%
“…Sometimes the fractional derivative is not discussed sufficiently: We have found literature that used fractional derivatives without stating the exact approach, e.g. [39]. But as stated and referenced in [32], we assume the Grünwald-Letnikov fractional derivative is the employed fractional derivative.…”
Section: Problemsmentioning
confidence: 99%
“…Moreover, the relationship between the dependent variable (SOM content) and the spectral data may not be purely linear due to the complex composition of soil properties. Machine learning methods, such as support vector machine regression, (SVMR), the back propagation neural network (BPNN), the cubist regression tree, random forests, and others, can be employed to address nonlinear problems [8,13,14]. The inherent structures of these methods makes it challenging for them to uncover the functional relationship between Vis-NIR spectra and the SOM.…”
Section: Introductionmentioning
confidence: 99%